If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 = 6x + -5 Reorder the terms: 115 = -5 + 6x Solving 115 = -5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 115 + -6x = -5 + 6x + -6x Combine like terms: 6x + -6x = 0 115 + -6x = -5 + 0 115 + -6x = -5 Add '-115' to each side of the equation. 115 + -115 + -6x = -5 + -115 Combine like terms: 115 + -115 = 0 0 + -6x = -5 + -115 -6x = -5 + -115 Combine like terms: -5 + -115 = -120 -6x = -120 Divide each side by '-6'. x = 20 Simplifying x = 20
| -3(x-5)+4x-1=18 | | 3x=4-5 | | 9x^2+36x+36=15x^2-31x-24 | | (X^2-3x)(x+15)=0 | | 23x+1=12x+34 | | 19=m-(-10) | | -3(-3x-5)-x-5=2 | | 2y-2x=12 | | 48-3y=3y-6 | | 42x+(-24)= | | 53=5x+13 | | 72-12a= | | -2x-13=3x+7 | | =(2x+5)(7x-3) | | -3+6x+4+(-9x)= | | 4(2z-1)-6(3-x)=-8 | | 21x^2+21x-23=0 | | -8x+6=-3x+16 | | 1/4-2/7=5/7 | | -10x-3=-6x-23 | | 8+6x=18+8x | | 3x+5y=05 | | 49-3y=3y-6 | | 6x=108.75 | | x^2-8x-4y^2+64y-1=0 | | 7x+11=12x+36 | | 3x+2(-2x+2)=6 | | X^4-5x^2-28x-84=0 | | -3h+8=2 | | 16x+8=-6x-25 | | -4+9x+9+(-11x)= | | 3x+11=-2x+6 |